Effect of incorporation of broccoli residues into soil on occurrence of verticillium wilt of spring-sowing-cotton and on rhizosphere microbial communities structure and function - Zhao, Weisong; Wang, Peipei; Dong, Lihong; Li, Shezeng; Lu, Xiuyun; Zhang, Xiaoyun; Su, Zhenhe; Guo, Qinggang; Ma, Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Cotton verticillium wilt (CVW) represented a typical plant soil-borne disease and resulted in widespread economic losses in cotton production. However, the effect of broccoli residues (BR) on verticillium wilt of spring-sowing-cotton was not clear. We investigated the effects of BR on CVW, microbial communities structure and function in rhizosphere of two cotton cultivars with different CVW resistance using amplicon sequencing methods. Results showed that control effects of BR on CVW of susceptible cultivar (cv. EJ-1) and resistant cultivar (cv. J863) were 58.49% and 85.96%, and the populations of V. dahliae decreased by 14.31% and 34.19%, respectively. The bacterial diversity indices significantly increased in BR treatment, while fungal diversity indices significantly decreased. In terms of microbial community composition, the abilities to recruit bacteria and fungi were enhanced in BR treatment, including RB41, Gemmatimonas, Pontibacter, Streptomyces, Blastococcus, Massilia, Bacillus, and Gibberella, Plectosphaerella, Neocosmospora, Aspergillus and Preussia. However, the relative abundances of Sphingomonas, Nocardioides, Haliangium, Lysobacter, Penicillium, Mortierella and Chaetomidium were opposite tendency between cultivars in BR treatment. According to PICRUSt analysis, functional profiles prediction showed that significant shifts in metabolic functions impacting KEGG pathways of BR treatment were related to metabolism and biosynthesis. FUNGuild analysis indicated that BR treatment altered the relative abundances of fungal trophic modes. The results of this study demonstrated that BR treatment decreased the populations of V. dahliae in soil, increased bacterial diversity, decreased fungal diversity, changed the microbial community structure and function, and increased the abundances of beneficial microorganisms.